A wind-blown bubble in the Central Molecular Zone cloud G0.253+0.016. Issue 4 (17th December 2021) - Henshaw, Jonathan D; Krumholz, Mark R; Butterfield, Natalie O; Mackey, Jonathan; Ginsburg, Adam; Haworth, Thomas J; Nogueras-Lara, Francisco; Barnes, Ashley T; Longmore, Steven N; Bally, John; Kruijssen, J M Diederik; Mills, Elisabeth A C; et al.
ABSTRACT: G0.253+0.016, commonly referred to as 'the Brick' and located within the Central Molecular Zone, is one of the densest (≈10 3–4 cm −3 ) molecular clouds in the Galaxy to lack signatures of widespread star formation. We set out to constrain the origins of an arc-shaped molecular line emission feature located within the cloud. We determine that the arc, centred on l_0, b_0 brace =0_.^° 248, 0_.^° 018 brace, has a radius of 1.3 pc and kinematics indicative of the presence of a shell expanding at 5.2^+2.7_-1.9 km s^-1 . Extended radio continuum emission fills the arc cavity and recombination line emission peaks at a similar velocity to the arc, implying that the molecular gas and ionized gas are physically related. The inferred Lyman continuum photon rate is N LyC = 10 46.0 –10 47.9 photons s −1, consistent with a star of spectral type B1-O8.5, corresponding to a mass of ≈12–20 M⊙ . We explore two scenarios for the origin of the arc: (i) a partial shell swept up by the wind of an interloper high-mass star and (ii) a partial shell swept up by stellar feedback resulting from in situ star formation. We favour the latter scenario, finding reasonable (factor of a few) agreement between its morphology, dynamics, and energetics and those predicted for an expanding bubble driven by the wind from a high-mass star. The immediate implication is that G0.253+0.016 may not be as quiescent as is commonly accepted. We speculate that the cloud may have produced a ≲10 3 M⊙ star cluster ≳0.4 Myr ago, and demonstrate that the high-extinction and stellar crowding observed towards G0.253+0.016 may help to obscure such a star cluster from detection.